2023
DOI: 10.3390/su151813337
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Emotional Advertising Appeals: Examining Their Influence on Consumer Purchasing Behavior and Brand–Customer Relationship

David Vrtana,
Anna Krizanova

Abstract: Irrationality is a strong phenomenon in consumer behavior that significantly impacts final purchase decisions. Through holistic approaches, companies have become more oriented towards emotional experiences. This study investigates the emotional impact of Dove brand advertising appeals on the frequency and intensity of emotions experienced by Slovak consumers. A theoretical framework was created for the conceptual development of emotional appeals in advertising and their impact on irrational purchasing behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Many companies are also focusing more on the emotional experience of the consumer. The design of emotionally appealing advertisements can evoke an emotional experience in consumers, which in turn can lead to positive purchasing decisions [29]. Research in the field of cognitive science has also confirmed this.…”
Section: The Mediating Role Of Emotional Experiencementioning
confidence: 90%
“…Many companies are also focusing more on the emotional experience of the consumer. The design of emotionally appealing advertisements can evoke an emotional experience in consumers, which in turn can lead to positive purchasing decisions [29]. Research in the field of cognitive science has also confirmed this.…”
Section: The Mediating Role Of Emotional Experiencementioning
confidence: 90%
“…Depending on how committed a client is to a business, promotional offers have varying effects on them. For ardent supporters, promotions bolster their perception of value and emotional connections (Vrtaňa & Křižanová, 2023;. Promotions bring in new customers, acquainting them with the brand and maybe establishing a lasting rapport (Casado & Erdmann, 2021).…”
Section: 5-brand and Promotional Influencementioning
confidence: 99%
“…Simultaneously, if the implantation form is not appropriate, such as one that has low integration with the plot, a long implantation time, or excessively prominent implantation images, it will affect the dissemination quality of the product placement and the audience's perception of the animation, causing aversion to the product and reducing favorability and purchase intention with respect to the brand [50]. Nevertheless, due to the popularity of high-profile brands, consumer preferences and purchase intentions are relatively fixed [51]. Therefore, the negative effects of the inappropriate placement of products made by high-profile brands in a single animation are relatively limited.…”
Section: Evaluation Of the Effect Of Product Placementmentioning
confidence: 99%